On Triangles With Fibonacci and Lucas Numbers as Coordinates - Čerin, Zvonko (Sarajevo Journal of Mathematics, 2024)
We consider triangles in the plane with coordinates of points from the Fibonacci and Lucas sequences. 2000 Mathematics Subject Classification. 11B39